2013
DOI: 10.1177/1049909113492411
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in Life in Patients With Progressive Supranuclear Palsy

Abstract: This exploratory study investigated meaning in life (MiL) in patients with progressive supranuclear palsy (PSP). In the "Schedule for Meaning in Life Evaluation" (SMiLE), respondents list individual MiL areas before rating their current satisfaction and importance with them (index of weighting [IoW], index of satisfaction [IoS], and index of weighted satisfaction [IoWS], range 0-100). A total of 38 patients with PSP completed the SMiLE (IoS: 68.6 ± 25.6, IoW: 79.6 ± 12.6, and IoWS: 69.2 ± 26.1). A representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The high levels reported in the SMILE total scores in both populations (> 80) are comparable with those found in other studies including different kind of populations: cancer patients (25,26), palliative care patients (27,28), and general populations (22,29). In all these studies, scores ranged between 70 and 80.…”
Section: Level Of Satisfaction In Mil: the Meaning-making Hypothesissupporting
confidence: 87%
“…The high levels reported in the SMILE total scores in both populations (> 80) are comparable with those found in other studies including different kind of populations: cancer patients (25,26), palliative care patients (27,28), and general populations (22,29). In all these studies, scores ranged between 70 and 80.…”
Section: Level Of Satisfaction In Mil: the Meaning-making Hypothesissupporting
confidence: 87%
“…We found that both “meaning” and “peace” subscores of the FACIT‐sp scale contributed to HRQOL, and these represent two important issues for people with PD. There is a growing body of literature on the importance of meaning in coping with chronic illnesses, and a loss of meaning may contribute to demoralization and even requests for medical aid in dying . Regarding peace, there is evidence that prayer, meditation, deep‐breathing, and other spiritual practices may be useful aids to coping and are commonly used by PD patients .…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al [ 7 ] highlighted that the existential wellbeing was at least as important as any other domain in predicting the overall perceived QOL for palliative patients. Numerous studies have shown that QOL at the end of life is closely linked to non-physical determinants [ 3 , 6 , 41 43 ]. In reviews focusing on the QOL domains that are important for incurably ill patients, Albers et al showed that spiritual/existential well-being was one of the most often cited domains [ 1 , 44 ].…”
Section: Discussionmentioning
confidence: 99%